2000
DOI: 10.1152/ajpregu.2000.278.1.r201
|View full text |Cite
|
Sign up to set email alerts
|

Bright light during lactation alters the functioning of the circadian system of adult rats

Abstract: To examine the role of light in the maturation of the circadian pacemaker, twelve groups of rats were raised in different conditions of exposure to constant bright light (LL) during lactation: both duration and timing of LL were varied. We studied the motor activity rhythm of the rats after weaning, first under LL and then under constant darkness (DD). In DD, two light pulses [at circadian time 15 (CT15) and CT22] were applied to test the response of the pacemaker. Greater exposure to LL days during lactation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…To establish effects of early light experience on the behaviour of C57BL ⁄ 6J mice kept in LD after weaning, we monitored their locomotor activity rhythms throughout the experiment. We found that, similar to the results obtained for Wistar rats and Swiss mice (11,12), the expression of the locomotor activity rhythm of our mice was affected by postnatal light experience. No differences in the phase of entrainment were observed between the groups, which suggests that the entraining mechanisms of the clock are not affected by early light experience.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To establish effects of early light experience on the behaviour of C57BL ⁄ 6J mice kept in LD after weaning, we monitored their locomotor activity rhythms throughout the experiment. We found that, similar to the results obtained for Wistar rats and Swiss mice (11,12), the expression of the locomotor activity rhythm of our mice was affected by postnatal light experience. No differences in the phase of entrainment were observed between the groups, which suggests that the entraining mechanisms of the clock are not affected by early light experience.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, LL‐reared mice showed low levels of VIP staining compared to LD‐ and DD‐reared mice. Because light responses are altered in LL‐reared animals (11, 12, 14, 16), we believe that these low levels may reflect a difference in how the light input is processed in the retinorecipient area of the SCN. However, no differences in the period or the phase of entrainment were found amongst groups, and the amplitude and stability of the circadian rhythm of locomotor activity were even increased in LL‐reared mice compared to LD‐ and DD‐reared mice, suggesting that the decrease in VIP expression observed in the SCN of LL‐reared mice: (i) is not sufficient to cause a major disruption of clock functioning and (ii) may activate compensatory mechanisms within the clock (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…SCN cultures from these animals express circadian oscillations of Per1-luc expression indefinitely, while oscillations in cultured peripheral tissues damp after several cycles (Yamazaki et al, 2000). The phases of central and peripheral circadian oscillators are held in specific relationships under light-dark (LD) cycles (Yamazaki et al, 2000;Abe et al, 1 To whom correspondence should be addressed: Michael Menaker Department of Biology, University of Virginia, Charlottesville, VA 22903; Tel: 434-982-5767; Fax: 434-982-5626; e-mail: mm7e@virginia Like SCN lesion, prolonged constant light (LL) exposure disrupts behavioral circadian rhythms in rodents, resulting first in an increase in circadian period and then in arrhythmicity (Honma et al, 1996, Benstaali et al, 2001Canal-Corretger et al, 2000). It has been suggested that this effect of LL might be the result of disrupting the coupling among SCN cells (Mason 1991; Zlomanazuck et al, 1991;Ohta et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We found that rats reared under LL develop a stable circadian rhythm under LL and that this rhythm is maintained throughout the lifespan of the animal (4). Specifically, we observed that the development of the adult's circadian rhythm under LL depended on the length of the exposure to LL during lactation (5) and that at least 12 days under LL during lactation were needed for it to develop.…”
Section: Discussionmentioning
confidence: 99%